The impact of native competitors on an alien invasive: temporal niche shifts to avoid interspecific aggression? - Harrington, L; Harrington, A; Yamaguchi, N; Thom, MD; Ferreras, P; Windham, T; Macdonald, D (2009)
The American mink, Neovison vison, is an established, alien invasive species in the United Kingdom that originally colonized the country at a time when two native mustelids (otters, Lutra lutra, and polecats, Mustela putorius) were largely absent. Both of these species are now recovering their populations nationally. We compared the relative abundance and the behavior of mink in the 1990s and in the 2000s in an area of southern England where both otters and polecats were absent in the 1990s but reappeared in the intervening years. We found that mink were still abundant in the 2000s in the presence of otters and polecats, but that they appeared to have altered some aspects of their behavior. In accordance with previous studies, we found that mink consumed fewer fish in the presence of otters. We also found that mink were predominantly nocturnal in the 1990s (in the absence of competitors) but were predominantly diurnal in the 2000s (in the presence of competitors). We hypothesize that this temporal shift may be an avoidance mechanism allowing the coexistence of mink with the otter and the polecat, although we are unable to attribute the shift to one or the other species. We also found that mink in the presence of competitors weighed less but remained the same size, suggesting the possibility of a competitor-mediated decline in overall body condition. This is one of very few field studies demonstrating a complete temporal shift in apparent response to competitors. The implications of this study are that recovering otter populations may not lead to significant and long-term reductions in the number of invasive mink in the United Kingdom as has been suggested in the media, although we cannot exclude the possibility of a decline in mink in the longer-term.